Asymmetric Total Synthesis of (−)‐Stemonamine and Its Stereochemical Stability. Issue 7 (16th January 2018) - Fujita, Satoshi; Nishikawa, Keisuke; Iwata, Takayuki; Tomiyama, Taishi; Ikenaga, Hiroshi; Matsumoto, Kenji; Shindo, Mitsuru
Abstract: The first asymmetric total synthesis of (−)‐stemonamine is described. The key reactions included intramolecular acylation to construct the seven‐membered ring and a tandem [2+2] cycloaddition‐Dieckmann condensation reaction using an ynolate to form the fully substituted cyclopentenone moiety. Racemization and epimerization of the natural product were first experimentally demonstrated. Abstract : A pioneering synthesis : The first total synthesis of nonracemic (−)‐stemonamine is achieved in 17 steps from known compounds. Key reactions include intramolecular acylation and ynolate‐initiated tandem [2+2] cycloaddition‐Dieckmann condensation.